Quality of Care Program Reduces Unplanned Health Care Utilization in Patients With Inflammatory Bowel Disease. (December 2021) - Melmed, Gil Y.; Oliver, Brant; Hou, Jason K.; Lum, Donald; Singh, Siddharth; Crate, Damara; Almario, Christopher; Bray, Harry; Bresee, Catherine; Gerich, Mark; Gerner, Donna; Heagy, Erica; et al.
Abstract : INTRODUCTION: There is significant variation in processes and outcomes of care for patients with inflammatory bowel disease (IBD), suggesting opportunities to improve quality of care. We aimed to determine whether a structured quality of care program can improve IBD outcomes, including the need for unplanned health care utilization. METHODS: We used a structured approach to improve adult IBD care in 27 community-based gastroenterology practices and academic medical centers. Patient-reported outcomes (PRO) and health care utilization were collected at clinical visits. Outcomes were monitored monthly using statistical process control charts; improvement was defined by special cause (nonrandom) variation over time. Multivariable logistic regression was applied to patient-level data. Nineteen process changes were offered to improve unplanned health care utilization. Ten outcomes were assessed, including disease activity, remission status, urgent care need, recent emergency department use, hospitalizations, computed tomography scans, health confidence, corticosteroid or opioid use, and clinic phone calls. RESULTS: We collected data prospectively from 20, 382 discrete IBD visits. During the 15-month project period, improvement was noted across multiple measures, including need for urgent care, hospitalization, steroid use, and opioid utilization. Adjusted multivariable modeling showed significant improvements over time across multiple outcomes including urgent care need, health confidence, emergency department utilization, hospitalization, corticosteroid use, and opioid use. Attendance at monthly coached webinars was associated with improvement. DISCUSSION: Outcomes of IBD care were improved using a structured quality improvement program that facilitates small process changes, sharing of best practices, and ongoing feedback. Spread of these interventions may facilitate broad improvement in IBD care when applied to a large population.